An Investigation of the Perceived Life Satisfaction and Social Support Levels of the Vocational High School for Hearing-Impaired Students According to Active Participation in Sports Activities - Mustafa Barış Somoğlu; Hamit Cihan (Journal of Educational Issues, 2024)
The aim of this article was to examine the perceived life satisfaction and social support levels of the vocational high school students according to active participation in sports activities with respect to some variables, and determine the relation between certain variables and involvement in sports. The study group of the research consisted of 554 students studying at various vocational high schools for hearing impaired during the 2014-2015 education year. The sample was composed of 327 male (60.1% of the sample) and 217 female (39.9% of the sample) students. “Personal Information Form”, “Multidimensional Scale of Perceived Social Support (MSPSS)” developed by G. D. Zimet, Dahlem, S. G. Zimet, and Farley (1988) and adapted to Turkish by Eker, Akar, and Yaldız (2001), and “The Satisfaction With Life Scale (SWLS)” developed by Diener, Emmons, Larsen, and Griffin (1985) and adapted to Turkish by Köker (1993), were used for data collection. The statistical methods and tools used for data evaluation were descriptive statistics, T-Tests for independent groups, one-way analysis of variance (one-way ANOVA), multi-way analysis of variance (multi-way ANOVA) and Tukey’s multiple comparison test. In order to determine the relationship between dependent variables, Pearson Correlation Test and Regression Test were administered. Based on the findings of study, the study group members tended to have over moderate social support and life satisfaction levels and there was a moderately positive correlation between the social support and life satisfaction levels. The perceived social support and life satisfaction levels of the students demonstrated significant differences in respect to the sportsmanship status, sport branches, active years of sports involvement. The study revealed that participation in sports activities play an important role on the perceived social support and life satisfaction levels of the vocational high school for the hearing-impaired students.